Research on Automotive Differential Test Rig and Analysis of Performance Test - Tao Zenan; Jia Jumin; Xu Aifen (Jixie chuandong)
The performance of differential has an important effect on vehicle passability and maneuverability. In order to determine the locking coefficient of the differential，a special test rig is developed，and a new test method is proposed. That is，the locking coefficient is measured under three working conditions of straight-line driving，low-speed turning and high-speed turning. The test results show that the locking coefficient of the differential is consistent with the theoretical value，the test results are accurate and reliable，and the performance test is completed well.